Combined computational approaches for developing new anti-Alzheimer drug candidates: 3D-QSAR, molecular docking and molecular dynamics studies of liquiritigenin derivatives. Issue 12 (December 2022) - Nour, Hassan; Daoui, Ossama; Abchir, Oussama; ElKhattabi, Souad; Belaidi, Salah; Chtita, Samir
Abstract: Butyrylcholinesterase is an acetylcholine-degrading enzyme involved in the memorization process, which is becoming an interesting target for the symptomatic treatment of Alzheimer's disease. In the present investigation, the structure–activity relationship of a set of Liquiritigenin derivatives recently revealed to be Butyrylcholinesterase inhibitors was studied basing on comparative field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMISA). As a result, performant models with high predictive capability have been developed (CoMFA model: R 2 = 0.91, Q 2 = 0.62, R 2 pred = 0.85; CoMISA model: R 2 = 0.92, Q 2 = 0.59, R 2 pred = 0.83) and implemented to design new Liquiritigenin derivatives with improved activity. Besides, the affinity of the designed derivatives towards the active site of Butyrylcholinesterase, was confirmed by molecular docking and molecular dynamics studies. Moreover, they exhibited good pharmacokinetics properties. Accordingly, the outcomes of the present investigations can provide important direction for the development of new anti-Alzheimer's drug candidates. Abstract : Alzheimer's disease; Butyrylcholinesterase; Liquiritigenin; CoMFA; CoMISA; Molecular docking; Molecular dynamics.